2010
DOI: 10.1523/jneurosci.0966-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Neural Modulation Tuning Characteristics Scale to Efficiently Encode Natural Sound Statistics

Abstract: The efficient-coding hypothesis asserts that neural and perceptual sensitivity evolved to faithfully represent biologically relevant sensory signals. Here we characterized the spectrotemporal modulation statistics of several natural sound ensembles and examined how neurons encode these statistics in the central nucleus of the inferior colliculus (CNIC) of cats. We report that modulation-tuning in the CNIC is matched to equalize the modulation power of natural sounds. Specifically, natural sounds exhibited a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
109
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(128 citation statements)
references
References 49 publications
19
109
0
Order By: Relevance
“…12 and 13), as predicted from previous single and multiunit studies (Atencio and Schreiner 2012;Cheung et al 2001;Eggermont et al 2011) and subcortical stations of the auditory pathway (Rodriguez et al 2010a(Rodriguez et al , 2010b. Our study builds on these prior studies because we demonstrated that reliable, phase-locked responses to sound features can be generated from ECoG-level signals.…”
Section: Discussionsupporting
confidence: 64%
“…12 and 13), as predicted from previous single and multiunit studies (Atencio and Schreiner 2012;Cheung et al 2001;Eggermont et al 2011) and subcortical stations of the auditory pathway (Rodriguez et al 2010a(Rodriguez et al , 2010b. Our study builds on these prior studies because we demonstrated that reliable, phase-locked responses to sound features can be generated from ECoG-level signals.…”
Section: Discussionsupporting
confidence: 64%
“…Although the physical causes of the power-law relationship observed in natural images and in natural sounds are unrelated, it is highly probable that similar neural efficiency principles apply in both sensory systems. And indeed, a similar decorrelation has been observed in the inferior colliculus where the gain of auditory neurons emphasizes higher temporal and spectral modulation effectively counterbalancing the 1/ f relationship observed in the modulation power spectrum (and not the sound spectrum) of natural sounds [24]. At higher levels of the auditory processing stream, it has been shown that the population of neurons have a maximum gain at intermediate modulation frequencies, in a region that is particularly useful for distinguishing among different natural sounds [25].…”
Section: Perceptually Relevant Physical Characteristics Of Isolated Nsupporting
confidence: 56%
“…Additional avian STRF types and examples can be found in [51,58,59]. Examples in the mammalian auditory system can be found in [24,[62][63][64].…”
Section: Resultsmentioning
confidence: 99%
“…We used both time and frequency representations to characterize the filtering performed on the envelope (Lesica and Grothe 2008b;Rodríguez et al 2010aRodríguez et al , 2010b. The time representation, called the MTRF, is the impulse response of the linear filter that relates the input amplitude modulation to the neuron's response (Fig.…”
Section: Resultsmentioning
confidence: 99%